PENDAMPINGAN PENGOLAHAN DAGING AYAM BERBASIS REMPAH LOKAL UNTUK OPTIMALISASI PRODUKTIVITAS USAHA TERNAK UNGGAS DI DESA SALAMREJO, BLITAR - David Kurniawan; Nur Agustin Mardiana; Anang Widigdyo; Rosidi Azis (CV. Denasya Smart Publisher, 2026)
This Community Service Program (PkM) focuses on solving the problems of low added value and market dependence among small-scale chicken farmers in Salamrejo Village, Blitar. Using a participatory action research and asset-based community development approach, the program was designed to integrate abundant local spice potential as raw materials for processing. The objectives are to enhance the technical and managerial capacity of the